Digital illustration appears on the scene: history of scientific illustration in Costa Rica, fifth part - Monge, Julián (2019)
In 2018 the National University (Heredia) joined the Costa Rican institutions active in the area of scientific illustration with projects focused on digital illustration, animation of current and extinct organisms, and three-dimensional printing of scientific and technical illustrations.